Law Enforcement in Efforts to Combat Cyber Crime in Indonesia Building Future Digital Security - Lesmana, Sri Jaya; Sofia , Inas; Felina, Felina (The International Journal of Law Review and State Administration, 2023)
The development of information technology can change social order and behavior. The wrong use of advances in information technology refers to crime. The level of cybercrime in Indonesia has reached an alarming stage, therefore the existence of a security system and regulations related to this matter is an urgent need. The purpose of this study is to examine and analyze law enforcement efforts in combating cybercrime in order to build future digital security in Indonesia. Normative legal research is used by researchers to answer related problems through a legal approach with a literature study method. The results showed that although cybercrime has been regulated in positive law in force in Indonesia, the regulation and implementation of security can be said to be still not optimal. Researchers suggest that cybersecurity-related regulations should be specific. Furthermore, harmonization and synchronization of related rules must be carried out so that the handling of cybercrime becomes integrated. Finally, the establishment of a special institution for handling cyber problems is important so that Indonesia has a strong cyber defense